Enhancing Teacher Awareness on Healthy Schools: A Community Services Initiative for Elementary and Junior High School Teachers in Bontang - Wisnuwardani, Ratih Wirapuspita; Irawan, Bambang; Ningsih, Riyan; Akbar, Paisal (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
A healthy school environment is vital in promoting the well-being of students, teachers, and the school community. This study aimed to enhance teachers' knowledge and implementation of healthy school practices through a community service program. The initiative involved socialization and training sessions targeting elementary and junior high school teachers in Bontang. The program was structured into three phases: preparation, implementation, and evaluation. Educational materials covering healthy school concepts, balanced nutrition, mental health, and environmental assessments were developed, followed by training conducted at Puri Senyiur Hotel, Samarinda, East Kalimantan, from December 1-4, 2024. A total of 83 teachers participated, receiving instruction from health experts. Knowledge assessments were conducted before and after training, analysed using the Wilcoxon test due to non-normal data distribution. Results showed a significant median difference of 20 in knowledge scores (p = 0.0001), indicating substantial improvement post-training. Although the assessment measured short-term effects, the findings suggest a positive increase in awareness. Regular teacher training on healthy schools is essential for preventing malnutrition and fostering better health practices among students. This initiative aligns with governmental efforts to promote healthy eating behaviors in schools. Sustaining such programs requires collaboration between healthcare professionals, universities, and other institutions, along with integrating nutrition education into school curricula.